2014
DOI: 10.1002/jhbp.107
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog pathway as a potential treatment target in human cholangiocarcinoma

Abstract: The results of our study suggest that the Hh pathway plays a relevant role at least in a subset of human CCC. Inhibition of this pathway may represent a possible treatment option for CCC patients in which the Hh pathway is activated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Gli-1/2 translocate to the nucleus, where they bind to the Gli-binding consensus element in target genes resulting in their activation. 11 Overexpression and aberrant activation of Hh signaling molecules have been demonstrated in 50-70% of hepatoblastomas, primary HCC and cholangiocyte carcinomas, 12,13 and the Smo antagonists, cyclopamine and GDC-0449 have been used to block the growth of hepatoma cell-derived xenografts in animal experiments. 12,14 However, no study is available focusing on whether overexpression of Hh molecules or enhancing Hh signaling activity is responsible for the highly metastatic behavior of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Gli-1/2 translocate to the nucleus, where they bind to the Gli-binding consensus element in target genes resulting in their activation. 11 Overexpression and aberrant activation of Hh signaling molecules have been demonstrated in 50-70% of hepatoblastomas, primary HCC and cholangiocyte carcinomas, 12,13 and the Smo antagonists, cyclopamine and GDC-0449 have been used to block the growth of hepatoma cell-derived xenografts in animal experiments. 12,14 However, no study is available focusing on whether overexpression of Hh molecules or enhancing Hh signaling activity is responsible for the highly metastatic behavior of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Hedgehog signaling plays a critical role in growth of digestive tract tumors (Berman et al 2003), and the subsequent reports showed the activation of Hedgehog signaling in hepatocellular carcinoma (Huang et al 2006;Al-Bahrani et al 2015;Dugum et al 2016) and cholangiocarcinoma (Kiesslich et al 2014;Riedlinger et al 2014). In fact, we have shown that GLI1 immunoreactivity was detected in 55% of hepatocellular carcinoma (21/38 specimens) and 86% of cholangiocarcinoma (6/7 specimens) (see Tables 2 and 5).…”
Section: Potential Role Of Hedgehog Signaling For Regulation Of Mitf mentioning
confidence: 54%
“…In the presence of a Hedgehog ligand, Smoothened enhances nuclear translocation of gliomaassociated transcription factors, such as glioma-associated oncogene 1 (GLI1) (Varjosalo and Taipale 2008), thereby mediating the Hedgehog signal. Moreover, GLI1 is expressed in the normal bile duct (Kiesslich et al 2014) and is overexpressed in hepatocellular carcinoma (Dugum et al 2016) and cholangiocarcinoma (Kiesslich et al 2014;Riedlinger et al 2014), suggesting that the Hedgehog signaling pathway may be activated in hepatic cancer cells. Considering the cyclopamine-mediated induction of MITF in hepatic cancer cell lines (Samatiwat et al 2016), we have hypothesized that the Hedgehog signaling may influence MITF expression in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…45 The hedgehog pathway as well as notchexpression and potential curcumin-treatment have recently been defined as candidates. 46,47 Zhu and associates demonstrated that the IL-6/Stat3-miR-17-92 cluster-PTEN signaling axis plays a decisive role in CCA tumor development and progression. 48 Fibroblast growth factor receptor 2 fusions and ERRFI gene mutations as well as up-regulation of HER-2 signaling have been identified as relevant genomic targets in some patients.…”
Section: Status Quomentioning
confidence: 99%